A New Method of Breakpoint Connection using Curve Features for Contour Vectorization - Zhao, Jianhui; Liang, Guozhong; Yuan, Zhiyong; Zhang, Dengyi (Elektronika ir Elektrotechnika, 2012)
Connection of break points is a vital and difficult problem during contour vectorization for digital image, such as scanned maps and engineering drawings. In this paper a novel algorithm is proposed for breakpoint connection using curve features. Three features including curve distance, tangent angle and average curvature, are defined and analyzed. Then the features are normalized and fused into one energy function to represent the connection probability. Based on the probability function, all candidate connections for one breakpoint are compared and the most suitable result is determined. With the help of image preprocessings including denoising, binarization and thinning, our method has been tested with experiments on real images, and the results prove its efficiency. DOI: http://dx.doi.org/10.5755/j01.eee.18.9.2813